Investigation of Human Electromagnetic Radiation Characteristic For Kidney Disease Patients - Zura A. Jalil, Siti; Nazerah Shamsuddin, Aimi; Armiza Mohd Aris, Siti; Aini Bani, Nurul; Mad Kaidi, Hazilah; Nabil Muhtazaruddin, Mohd; Usman, Sahnius; Azri Mohd Izhar, Mohd; Yusuf, Rihana; Syilawani S. Abdul Kadir, Ros (International Journal of Engineering and Technology, 2018)
The human body is shown to have their own radiation that emits at certain frequencies into the space surround the body. The purpose of this paper is to investigate the characteristic of human electromagnetic radiation among kidney disease patients and non-kidney disease participants. The body radiation frequencies are measured using body radiation wave detector at twenty-two points of the human body. The properties of human electromagnetic radiation are evaluated using statistical analysis of dependent t-test of Wilcoxon Signed Rank test and independent t-test of Mann-Whitney U test. Significant results with the Sig. value below 0.05 are shown in lower body, torso, chakra, arm and upper body, thus indicates the characteristic differences of human electromagnetic radiation frequency between kidney disease patients and non-kidney disease participants.Â Â